Sound absorption characteristics of loose bituminous coal porous media with different metamorphic degrees. (15th January 2023) - Ren, Shuai-Jing; Ma, Teng; Zhang, Yan-Ni; Deng, Jun; Xiao, Yang; Zhai, Xiao-Wei; Zhang, Yu-Tao; Song, Ze-Yang; Wang, Cai-Ping
Highlights: Variation in sound absorption is studied based on the structural properties of coal. Sound waves mainly propagate along the voids in loose coal. Loose coal belongs to the high absorption medium of sound waves. The obtained peak frequency provides basis for the selection of the acoustic signal. Abstract: With the advantages of high applicability and reliability, the acoustic detection method has been widely used in the field of temperature measurement, positioning, and flaw detection. To apply acoustic temperature measurement techniques to the detection of high temperature points of loose coal spontaneous combustion, the basic acoustic properties of loose coal need to be clarified. Four bituminous coals with different degrees of metamorphosis were selected for the study. The stacking structural characteristics of loose coal were studied by industrial computerized tomography. The sound absorption coefficient of loose coal was tested based on the sound absorption test system. The results revealed that with the increase of particle size, the voids of loose coal gradually became larger and the connectivity became better. The distribution characteristics of voids in loose coal were intrinsic to the variation in sound absorption coefficients. The sound absorption coefficient was more influenced by the particle size and stack thickness than by the degree of deterioration. Except for the particle size of less than 0.9 mm and the stacked thickness of 2 cm coal samples, the absorption coefficients of the coal samples increased gradually with decreasing particle size at the same acoustic frequency, and the peak absorption coefficients gradually shifted towards lower frequencies with increasing thickness. The peak frequency range of the absorption coefficient was calculated to provide a basis for the selection of the frequency band of the acoustic temperature measurement signal for loose coal.